Reliable detection of subchromosomal deletions and duplications using cell‐based noninvasive prenatal testing. (19th November 2018) - Vossaert, Liesbeth; Wang, Qun; Salman, Roseen; Zhuo, Xinming; Qu, Chunjing; Henke, David; Seubert, Ron; Chow, Jennifer; U'ren, Lance; Enright, Brennan; Stilwell, Jackie; Kaldjian, Eric; et al.
Abstract: Objective: To gather additional data on the ability to detect subchromosomal abnormalities of various sizes in single fetal cells isolated from maternal blood, using low‐coverage shotgun next‐generation sequencing for cell‐based noninvasive prenatal testing (NIPT). Method: Fetal trophoblasts were recovered from approximately 30 mL of maternal blood using maternal white blood cell depletion, density‐based cell separation, immunofluorescence staining, and high‐resolution scanning. These trophoblastic cells were picked as single cells and underwent whole genome amplification for subsequent genome‐wide copy number analysis and genotyping to confirm the fetal origin of the cells. Results: Applying our fetal cell isolation method to a series of 125 maternal blood samples, we detected on average 4.17 putative fetal cells/sample. The series included 15 cases with clinically diagnosed fetal aneuploidies and five cases with subchromosomal abnormalities. This method was capable of detecting findings that were 1 to 2 Mb in size, and all were concordant with the microarray or karyotype data obtained on a fetal sample. A minority of fetal cells showed evidence of genome degradation likely related to apoptosis. Conclusion: We demonstrate that this cell‐based NIPT method has the capacity to reliably diagnose fetal chromosomal abnormalities down to 1 to 2 Mb in size. Abstract : What is already known about this topic? Fetal trophoblastic cells can be isolated from maternal blood and be used for the detection of fetal aneuploidies and copy number variants. The data on the detection of subchromosomal deletions and duplications is currently limited. What does this study add? Cell‐based NIPT can be used for the detection of copy number abnormalities of greater than or equal to 1 Mb in the fetus by low‐coverage next‐generation sequencing after single cell whole genome amplification. Data are provided here for five cases in which different subchromosomal deletions and duplications ranging from 1.2 to 18.9 Mb were detected in single cells.